Subjective Well-Being in Muslim Students: The Role of Islamic Spirituality and Self-Efficacy - Susanti, Rita; Ikhwanisifa, Ikhwanisifa; Damayanti, Indah (Psikis : Jurnal Psikologi Islami, 2025)
Subjective well-being has become an important concern for Muslim students. Various challenges—including academic problems and pressure, social demands, changes in learning styles after COVID-19, economic issues, and uncertainty about the future—make students vulnerable to psychological and mental health problems. As a result, approaches that focus on psychological and spiritual factors as internal strengths are expected to help students cope with these challenges. Studies show that subjective happiness impacts an individual’s mental health and success in learning. One of the ways Muslims enhance their subjective well-being is through Islamic spirituality and self-efficacy. This research aimed to empirically examine the effect of Islamic spirituality and self-efficacy on subjective well-being among Muslim students. This study employed a quantitative research method with a correlational approach. Using a random cluster technique, the research participants were 360 Muslim students at one of the Islamic universities in Pekanbaru, Indonesia. The data were obtained using four standardized scales: the Islamic Spirituality Scale, the Subjective Well-Being Scale, the Scale of Positive and Negative Experience (SPANE), and the Self-efficacy Scale. The data was analyzed using multiple regression. The results showed a significant influence of Islamic spirituality and self-efficacy on students’ subjective well-being, with a calculated F value of 33.473 and a p-value of 0.000 (≤0.05). When students’ scores on spirituality and self-efficacy are high, their subjective well-being is high, and vice versa. The analysis of the influence of each variable showed a beta coefficient for spirituality of 0.059 and self-efficacy of 0.636. This means that self-efficacy has a more significant influence compared to Islamic spirituality